MAD or MADness? - Faletra, Francesco Fulvio; Sgarito, Giuseppe; Parisi, Francesca; Franca, Eluisa La; Mulè, Massimiliano; Carvelli, Alessandra; Di Stefano, Giovanni; Borrello, Rita Laura; Nuzzi, Vincenzo; Manca, Paolo; Cipriani, Manlio (Cardiovascular ultrasound, 2025)
Mitral valve prolapse (MVP) is a common condition affecting approximately 3% of the population, typically with a benign clinical course. However, a small subset of patients (5-10%) may develop severe mitral regurgitation or arrhythmias, which can lead to sudden cardiac death (SCD). Among the morphological features of MVP, mitral annular disjunction (MAD) has emerged as a potential marker of malignant MVP, with some studies suggesting an association with ventricular arrhythmias and SCD. MAD refers to a structural abnormality where there is a separation between the posterior mitral annulus and the ventricular myocardium, particularly during systole. Initially described in the 1980s, MAD has been primarily studied through echocardiography, although its dynamic nature during the cardiac cycle has complicated its diagnosis. The clinical significance of MAD has been debated, as its presence is not exclusive to pathological MVP, being observed in structurally normal mitral valves as well. Recent research, using advanced imaging techniques such as three-dimensional echocardiography, cardiac magnetic resonance and computed tomography, has provided a more refined understanding of MAD. These studies suggest that MAD can be found in normal hearts, particularly in the posterior mitral annulus, and is often considered a benign anatomical variant. However, the occurrence of MAD in patients with MVP, especially those with leaflet redundancy, has been linked to an increased risk of arrhythmias and SCD. The exact role of MAD in arrhythmogenesis remains unclear, but it is hypothesized that MAD may contribute to electrical instability by altering the mechanical properties of the mitral valve, potentially promoting fibrosis in the surrounding myocardium. Despite these associations, the direct causal role of MAD in SCD requires further investigation, and it may ultimately prove to be an innocent bystander rather than the primary cause of fatal arrhythmias.